De novo mutation of emopamil binding protein (EBP) gene in a girl with Conradi‐Hünermann‐Happle syndrome. Issue 8 (28th June 2019) - Soler‐Cardona, Ana; Brandau, Oliver; Laccone, Franco; Tanew, Adrian; Radakovic, Sonja
Abstract: Conradi‐Hünermann‐Happle syndrome is a rare X‐linked dominant syndrome affecting the skin, skeletal system, and eyes. Here, we report on a female patient with a de novo heterozygous missense mutation c.301C>T (p.Trp101Arg) of the EMP (emopamil binding protein) gene. Abstract : Conradi‐Hünermann‐Happle syndrome is a rare X‐linked dominant syndrome affecting the skin, skeletal system, and eyes. Here, we report on a female patient with a de novo heterozygous missense mutation c.301C>T (p.Trp101Arg) of the EMP (emopamil binding protein) gene.